Building futures : technology, ecology, and architectural practice - Garber, Richard, 1971-; Ohio Library and Information Network (Hoboken, New Jersey : John Wiley & Sons, Inc., 2023)
"Hurricanes, wildfires, social justice, global pandemic -- all of these current crises have transformed our relationship to the built environment at multiple scales, with technology at the center of enabling an architectural response. These require a re-positioning of architecture, both as an augmentation of technology and a reimaging of our professional role. Building Information Modeling (BIM) has been touted as the practice-based solution for the next generation of architects and designers. While BIM has been used by many to address architectural challenges of the past 50 years, today's BIM systems are robust and advanced enough to consider, incorporate, and address ecological and social sustainability issues. This book explores how our buildings can engage future realities and abstract concepts, ranging from climate change to public health crises. BIM Futures demonstrates a path in which BIM and related technologies such as simulation can be utilized in today's shifted context, by focusing on a more conceptual, and contemporary, way of thinking about design and practice. Organized into three sections around technology, environment, and architectural practice, the book includes diverse project examples and case studies highlighting each concept and exploring the interconnections between the broader areas. Moving beyond a basic understanding of the role of computation in architecture and design, it shows how to think critically and speculatively about technology's deeper and more lasting impact and promise, both for architects and society"--
Technology -- Ecology -- Architectural practice
Includes bibliographical references and index
Keywords: Architectural design -- Computer simulation; Architecture -- Computer simulation; Building information modeling; Architecture -- Environmental aspects; Technology -- Social aspects